1993
DOI: 10.1002/dc.2840090511
|View full text |Cite
|
Sign up to set email alerts
|

Fine‐needle aspiration biopsy of langerhans histiocytosis (histiocytosis‐x)

Abstract: A series of 14 fine-needle aspiration biopsies (FNAB) from histologically proven cases of histiocytosis-x (Hx) were reviewed. The smears revealed a variable mixture of Langerhans cells, eosinophils, macrophages, polymorphonuclear cells, and giant cells. Based on the predominant cells present, the cases were further categorized as Langerhans cell predominant (nine cases), eosinophil predominant (two cases), and macrophage predominant (three cases). Langerhans cells were usually polygonal without significant evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 18 publications
0
28
0
Order By: Relevance
“…Regardless of anatomic site, aspirates of any of the 3 forms of LCH are characterized by a predominance of LCs in a background of blood, and variable numbers of eosinophils, neutrophils, multinucleated giant cells, macrophages, and capillary fragments [28,29,30,31,32,33]. While LCs sometimes form loose cell groups surrounding transgressing blood vessels, they are most often present as isolated cells as seen in the 3 aspirates that we describe.…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of anatomic site, aspirates of any of the 3 forms of LCH are characterized by a predominance of LCs in a background of blood, and variable numbers of eosinophils, neutrophils, multinucleated giant cells, macrophages, and capillary fragments [28,29,30,31,32,33]. While LCs sometimes form loose cell groups surrounding transgressing blood vessels, they are most often present as isolated cells as seen in the 3 aspirates that we describe.…”
Section: Discussionmentioning
confidence: 99%
“…In the early phase, the lesions are characterised by a markedly cellular aspirate with large numbers of LCs (LC predominant pattern) or eosinophils (eosinophil predominant pattern) [20]. The later phase includes a relatively increased number of secondary cells, notably macrophages with a foamy cytoplasm (macrophage predominant pattern), and giant cells are also seen [20].…”
Section: Discussionmentioning
confidence: 99%
“…There is a transient decrease in the number of LCs. With further progression of the lesions, fibrosis increases with a decrease in the cellular component [20]. This stage resembles chronic non-specific inflammation with fibrosis where a specific diagnosis becomes highly challenging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Akhtar et al have reported that the degree of eosinophilic infiltrate in cytology specimens varies from scant to abundant in different areas of LCH lesions and also in different organs. However, presence of eosinophils or Charcot-Leyden crystals is a subtle feature that should alert the pathologist to include LCH in the differential diagnosis [26,27]. Onsite adequacy assessment with procurement of extra material for ancillary studies is helpful in clinching the diagnosis of this rare entity in thyroid FNA specimens.…”
Section: Fine Needle Aspiration and Biopsymentioning
confidence: 99%